2008
DOI: 10.1007/s11239-008-0230-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled trial to evaluate the tolerability, safety, pharmacokinetics, and pharmacodynamics of a potent inhibitor of poly(ADP-ribose) polymerase (INO-1001) in patients with ST-elevation myocardial infarction undergoing primary percutaneous coronary intervention: results of the TIMI 37 trial

Abstract: The results from this first trial of INO-1001 in STEMI support future investigation of INO-1001 as a novel treatment for reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 15 publications
(24 reference statements)
1
50
0
1
Order By: Relevance
“…This single randomized trial assessed the effect of the PARP1 inhibitor INO-1001 in 40 patients with myocardial infarction, undergoing percutaneous coronary revascularization (Morrow et al, 2009). While this study was not powered to assess clinical efficacy, there was a trend towards blunting of inflammatory response, as assessed by serial plasma c-reactive protein and IL-6 levels, with the addition of the PARP1 inhibitor.…”
Section: Parp1 Inhbitors As a Strategy For Selective Modulation Of Trmentioning
confidence: 99%
“…This single randomized trial assessed the effect of the PARP1 inhibitor INO-1001 in 40 patients with myocardial infarction, undergoing percutaneous coronary revascularization (Morrow et al, 2009). While this study was not powered to assess clinical efficacy, there was a trend towards blunting of inflammatory response, as assessed by serial plasma c-reactive protein and IL-6 levels, with the addition of the PARP1 inhibitor.…”
Section: Parp1 Inhbitors As a Strategy For Selective Modulation Of Trmentioning
confidence: 99%
“…Multiple lines of follow-up studies have confirmed and extended these findings and demonstrated the protective effects of PARP1 genetic deficiency, as well as of various classes of PARP inhibitors (including 3-aminobenzamide, nicotinamide, PJ34 and INO-1001) in various models of acute and chronic myocardial insults, including ischaemia/reperfusion injury, transplantation and chronic heart failure (see: Szabó et al, 2004;Booz, 2007;Pacher and Szabó, 2008;Berger et al, 2018). The concept of cardioprotection mediated by PARP inhibition has also been tested in a small clinical trial, where trends for anti-inflammatory and cardioprotective effects were noted in patients with myocardial infarction (Morrow et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a pig model, INO-1001 improved functional recovery after ischemia but did not affect infarct size (97). In humans, this agent reduced C-reactive and interleukin-6 levels in myocardial infarction (98) and caused myelosuppression and transaminitis when combined with temozolamide in patients with advanced melanoma (99).…”
Section: Clinical Datamentioning
confidence: 99%